2018
DOI: 10.1002/we.2206
|View full text |Cite
|
Sign up to set email alerts
|

On gradient‐based optimization of jacket structures for offshore wind turbines

Abstract: Aims and ScopeWind power is one of the major energy resources that are important components of future energy scenarios. Wind Energy offers a major forum for the reporting of advances in this rapidly developing technology with the goal of realising the world-wide potential to harness clean energy from land-based and offshore wind. The journal aims to reach all those with an interest in this field from academic research, industrial development through to applications, including individual wind turbines and compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…In particular, some recent studies have demonstrated the viability and, in most cases, advantages of analytical sensitivities in gradient-based formulations. This has been shown for static ), quasi-static (Oest et al, 2017 and dynamic (Chew et al, 2016) loading conditions (see also Oest et al (2018) for a comparison of these three approaches). In general, these approaches make the design optimization problem more efficient and stable, 35 3 https://doi.…”
mentioning
confidence: 63%
“…In particular, some recent studies have demonstrated the viability and, in most cases, advantages of analytical sensitivities in gradient-based formulations. This has been shown for static ), quasi-static (Oest et al, 2017 and dynamic (Chew et al, 2016) loading conditions (see also Oest et al (2018) for a comparison of these three approaches). In general, these approaches make the design optimization problem more efficient and stable, 35 3 https://doi.…”
mentioning
confidence: 63%
“…The boundaries are chosen conservatively by means of quite narrow design variable ranges (see Table 1), i.e., meaningful parameters that do not exhaust the possible range given by the structural code checks, in a realistic range around the values of the OC4 jacket (Popko et al, 2014). Only three-or four-legged structures with three, four, and five bays are regarded as valid solutions for this study.…”
Section: Boundaries Of Design Variables and Other Parametersmentioning
confidence: 99%
“…Oest et al (2018) presented a jacket optimization study, where different simulation codes were deployed to perform structural code checks. All mentioned works, except for the last one, represent tube sizing algorithms applied to the Offshore Code Comparison Collaboration Continuation (OC4) jacket substructure (Popko et al, 2014) for the National Renewable Energy Laboratory (NREL) 5 MW reference turbine (Jonkman et al, 2009), 3 where the initial structural topology is maintained even in the case of a strong tube diameter and wall thickness variations. Furthermore, it can be stated that all proposals share the entire mass of the jacket as an objective function to be minimized, which is meaningful in terms of tube sizing.…”
Section: Introductionmentioning
confidence: 99%
“…Employing the genetic algorithm (GA), Ma et al [14] optimized a 100 m PC tower system for a 5 MW wind turbine and discussed the advantages of a PC wind turbine tower. Oest et al [15] explored three different state-of-the-art analytical gradient-based optimization approaches to minimize the mass of a jacket structure for wind turbines considering fatigue and frequency constraints and provided insight into critical structural and modeling parameters. Adopting GA, Chen et al [16] suggested that the optimal height of the concrete segment should be 80.5 m for one 120 m PCSH wind turbine tower.…”
Section: Introductionmentioning
confidence: 99%